Political Clientelism, Family Power and Conflict Permanence in Pilkada - Kelihu, Ardiman (PCD Journal, 2022)
This article examines the relationship between political clientelism and the establishment of family power in local elections. It argues that the use of clientelism networks impacts the creation of family power, the application of which results in the perpetuation of social conflict. Clientelism networks serve as ready-to-use networks which can be mobilised to support relatives during political events. This article uses the case of local elections in Central Maluku (2007–2017) to show the clientelist processes used by the relatives of Tuasikal. The use of alternate clientelism networks enabled the Tuasikal family in Central Maluku to successfully establish power and perpetuate conflicts between supporters and opponents. This study used field observations to collect data in fifteen villages, focusing on the elites and community members involved in the 2007, 2012, and 2017 elections, as well as a review of relevant literature. This study concludes that clientelist practices are used to create political networks to maintain family power and perpetuate conflict between opposing community groups during elections.